Preparation method of self-repairing and self-early-warning polymer coating of MOF-based magnesium alloy
By using MOF nano containers with load corrosion inhibitors and early warning agents in magnesium alloy coatings, the problems of poor corrosion resistance of magnesium alloys and difficult to detect corrosion positions in a timely manner are solved, and the self-repair and self-warning functions are realized, which improves the corrosion resistance and scope of application of magnesium alloys.
Patent Information
- Application Number
- CN202411709356.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-28
AI Technical Summary
Magnesium alloys have poor corrosion resistance, and conventional polymer coatings are difficult to maintain anti-corrosion effect for a long time in harsh environments, and it is difficult to detect corrosion locations in time.
Using MOF nano containers as the key component of the coating, load corrosion inhibitors and early warning agents into the MOF, and add wetting agents to the coating to achieve self-healing and self-warning functions.
It improves the long-term corrosion resistance of magnesium alloys, can detect corrosion points in time, improves the stability and uniformity of the coating, is suitable for harsh environments, and reduces production costs.
Smart Images

Figure CN119529672A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of corrosion and protection technology, and in particular to a method for preparing a MOF-based magnesium alloy self-repairing and self-warning polymer coating. Background Art
[0002] As the lightest structural metal material, magnesium alloy has good machinability, ductility, casting ability and good electromagnetic shielding properties. It has been widely used in aerospace, automobile transportation and 3C electronics. However, compared with other traditional metal materials, magnesium alloy has poor corrosion resistance and usually needs to be improved through surface treatment technology. Polymer coating is widely used as a corrosion protection method with simple process and significant performance. As a physical barrier layer, it can effectively resist the attack of harmful species such as acid, alkali and salt ions, thereby effectively improving the corrosion resistance of magnesium alloy. However, the soluble salts and hydrophilic groups in the polymer coating react with water to form a liquid transmission path. The liquid containing chloride ions penetrates into the substrate interface through the transmission path in the coating and corrodes at the interface. Because the corrosion product is hygroscopic, an osmotic pressure is generated between the interface and the external corrosive medium, causing the water in the corrosive medium to continuously penetrate into the interface. Finally, the local volume of the coating expands and bubbles are generated, which eventually leads to comprehensive delamination failure.
[0003] Metal organic frameworks (MOFs) are porous coordination polymers composed of metal ions and organic ligands through coordination bonds. They have the advantages of large specific surface area, adjustable microstructure, and stability. Due to their highly adjustable porosity, large intrapore volume, and abundant action sites, they are widely used in the fields of biosensing, drug delivery, and catalysis. At present, there have been reports that MOFs are used as nanocapsule fillers to improve the anti-corrosion ability of coatings. Patent application number 202410459002.0 proposes a preparation method and use of a self-healing anti-corrosion coating based on MOF composite fillers. This method introduces MOF nanoparticles covered with an organic photothermal layer and loaded with corrosion inhibitors into the anti-corrosion coating to construct a self-healing anti-corrosion coating system. When the coating is damaged, light can promote the rapid release of the corrosion inhibitor in the MOF composite filler. At the same time, MOF can be transformed into an LDH film on the exposed metal surface to prevent the penetration of corrosive media and inhibit metal corrosion, thereby restoring the protective effect on metal materials. However, the presence of the organic photothermal layer may cause MOF to decompose prematurely and release the loaded substance inside the coating. In addition, the function of the coating is relatively single, and the corrosion location of the coating cannot be discovered in time.
[0004] In response to the current problems, a new type of MOF nanocontainer was designed and directly mixed into the coating. By loading the corrosion inhibitor and early warning agent into the MOF at the same time, the coating is endowed with self-repair and self-warning functions, which facilitates the timely detection of the damage location of the coating. In addition, the addition of a wetting agent to the coating helps to evenly disperse the MOF in the coating, ensure the stability of the coating, and simplify the coating preparation process. This innovation enables the coating to be used in various harsh environments and expands the scope of application of magnesium alloys in practical applications. Summary of the invention
[0005] In view of the problems that conventional polymer coatings have poor corrosion resistance and corrosion problems are difficult to detect in time, the present invention provides a method for preparing a MOF-based magnesium alloy self-repairing and self-warning polymer coating, which effectively solves the problems of poor corrosion resistance of magnesium and its alloys and limited long-term corrosion protection provided by conventional polymer coatings.
[0006] A method for preparing a MOF-based magnesium alloy self-repairing and self-warning polymer coating. The specific preparation steps are as follows:
[0007] (1) Magnesium alloy pretreatment: The magnesium alloy sample was cut into a size of 40 mm × 40 mm × 5 mm. The polished substrate was cleaned and dried with deionized water to remove the machining marks on the surface and set aside;
[0008] (2) Preparation of MOF: Dissolve zinc nitrate and 2-methylimidazole in an organic solvent respectively and stir for 10 minutes. Then add a corrosion inhibitor to the zinc nitrate solution, stir for 10 minutes, and adjust the pH value to 5 to obtain solution A. Add an early warning agent to the 2-methylimidazole solution, stir for 10 minutes, and adjust the pH value to 7 to obtain solution B. Slowly pour solution A into solution B, mix and stir for 30 minutes, and then let it stand for 12 hours. Centrifuge the suspension and collect the precipitate.
[0009] (3) MOF modification: The surfactant was dissolved in an organic solvent, and then the MOF prepared in step 2 was added, and heated and stirred for 6 hours. The solution was centrifuged, dried, collected, ground and sieved to obtain a MOF nanocontainer.
[0010] (4) Preparation of corrosion-resistant polymer coating on magnesium alloy: Add the MOF nanocontainer obtained in step 3 to the varnish and disperse it evenly in the coating solution by ultrasound to obtain a corrosion-resistant coating solution. Spray the solution on the surface of the magnesium alloy sample and let it stand at room temperature for 24 hours. Then, place the sample in a 60°C oven and dry it for 24 hours to complete the preparation of the corrosion-resistant polymer coating on the magnesium alloy.
[0011] Preferably, the polishing method described in step (1) is to polish the surface of the magnesium alloy substrate using water-abrasive sandpaper with a roughness of 240#, 400#, 600#, 800#, 1000#, and 2000# in sequence until the surface of the magnesium alloy substrate is smooth and flat.
[0012] Preferably, the organic solvent described in step (2) is one or a mixture of methanol, ethanol, and ethylene glycol; the corrosion inhibitor is one or more of succinic acid, benzotriazole, methionine, tartaric acid, and 8-hydroxyquinoline; the early warning agent is one or more of phenolphthalein, rhodamine, and phenol blue reagent; and the surfactant is one or more of sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, sodium dodecyl sulfonate, and sodium lauryl sulfate.
[0013] Preferably, sodium hydroxide or nitric acid is used to adjust the pH in step (2).
[0014] Preferably, the contents of the drugs used to prepare the MOF nanocontainer in steps (2) and (3) are as follows: 5-20 g / L zinc nitrate, 5-50 g / L 2-methylimidazole, 1-5 g / L corrosion inhibitor, 1-5 g / L early warning agent, and 1-20 g / L surfactant.
[0015] Preferably, the grinding and sieving method in step (3) is to use an agate grinding mortar to grind the MOF particles for 20 minutes, and then sieve the particles using a sieve with a particle size of 3000 mesh.
[0016] Preferably, the drying method described in step (3) is to use a vacuum drying oven to dry the powder, the setting temperature of the vacuum drying oven is 60-100° C., and the heating time is 4-6 hours.
[0017] Preferably, the ratio of various substances in the corrosion-resistant coating solution described in step (4) is: MOF particles are 1-10g / L.
[0018] Preferably, the spraying method described in step (3) is aerosol spraying, and the process parameters are: air pressure 0.2-0.4Mpa, spraying distance 100-300mm, flow rate 20-100mL / min, atomizing nozzle 1.3-2.0mm, spray gun speed 50-400mm / s, and coating spraying times 1-10 times.
[0019] Preferably, the magnesium alloy corrosion-resistant polymer coating described in step (4) is prepared, and the thickness of the polymer coating is 10-50 μm.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The present invention provides a method for preparing a MOF-based magnesium alloy self-repairing and self-warning polymer coating. The MOF doped in the coating does not affect the stability of the coating. At the same time, this method gives the coating a self-repairing function and a self-warning function, thereby improving the long-term corrosion resistance of the magnesium alloy and timely detecting corrosion points. The modified MOF nanocontainer is easier to disperse, which improves the quality of the coating. The polymer coating after the improved process has a uniform thickness, no obvious defects on the surface, excellent resistance to external damage, and excellent corrosion resistance. It can serve for a long time in harsh environments. At the same time, the preparation process of the present invention is simple, easy to operate, low cost, low equipment requirements, and easy to mass produce and prepare complex workpieces. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The disclosure of the present invention is described with reference to the accompanying drawings. It should be understood that the drawings are only for illustrative purposes and are not intended to limit the scope of protection of the present invention. In the accompanying drawings, the same reference numerals are used to refer to the same components. Among them:
[0023] Figure 1 This is a microscopic morphology of the MOF nanocontainer of the present invention;
[0024] Figure 2 Impedance diagram of magnesium alloy polymer coating provided by an embodiment of the present invention;
[0025] Figure 3 The impedance diagram of the magnesium alloy polymer coating provided for the comparative example of the present invention;
[0026] Figure 4 This is a UV-visible absorption spectrum of the early warning agent released by the polymer coating during long-term immersion provided by an embodiment of the present invention. DETAILED DESCRIPTION
[0027] It is easy to understand that according to the technical solution of the present invention, without changing the essential spirit of the present invention, a person skilled in the art can propose a variety of interchangeable structural modes and implementation modes. Therefore, the following specific implementation modes and drawings are only exemplary descriptions of the technical solution of the present invention, and should not be regarded as the whole of the present invention or as a limitation or restriction to the technical solution of the present invention.
[0028] Embodiment 1:
[0029] A method for preparing a MOF-based magnesium alloy self-repairing and self-warning polymer coating, the specific steps are as follows:
[0030] (1) Magnesium alloy pretreatment: The magnesium alloy sample was cut into a size of 40 mm × 40 mm × 5 mm by wire cutting. The substrate was polished, rinsed and dried to remove machining marks on the surface of the magnesium alloy substrate and then set aside.
[0031] (2) Preparation of MOF: Weigh 8 g / L zinc nitrate and 20 g / L 2-methylimidazole and dissolve them in methanol respectively, and stir for 10 min. Then add 4 g / L succinic acid to the zinc nitrate solution, stir for 10 min, and adjust the pH value to 5 to obtain solution A; add 2 g / L phenolphthalein reagent to the 2-methylimidazole solution, stir for 10 min, and adjust the pH value to 9 to obtain solution B. Slowly pour solution A into solution B, mix and stir for 30 min, then let stand for 12 h, and centrifuge the solution to collect the sediment;
[0032] (3) MOF modification: 10 g / L sodium dodecyl sulfate was dissolved in ethanol, and then the MOF prepared in step 2 was added and heated and stirred for 6 h. The solution was centrifuged, dried, collected, ground and sieved to obtain a MOF nanocontainer;
[0033] (4) Preparation of corrosion-resistant polymer coating on magnesium alloy: 2 g / L MOF nanocontainer was added to the varnish and uniformly dispersed in the coating solution by ultrasound to obtain a corrosion-resistant coating solution. This solution was sprayed on the surface of the magnesium alloy sample to prepare a coating with a thickness of 20 μm and allowed to stand at room temperature for 24 h. Subsequently, the sample was placed in an oven at 60 °C and dried for 24 h to complete the preparation of the corrosion-resistant polymer coating on the magnesium alloy.
[0034] The microscopic morphology of the MOF nanocontainer in the preparation method of a MOF-based magnesium alloy self-repairing self-warning polymer coating provided in this embodiment is as follows: Figure 1 As shown, the impedance diagram of the corrosion-resistant early warning polymer coating immersed in 3.5wt.% NaCl solution for 300 days is as follows Figure 2 As shown, the coating releases the warning agent UV after immersion for 500 days.
[0035] Embodiment 2:
[0036] A method for preparing a MOF-based magnesium alloy self-repairing and self-warning polymer coating, the specific steps are as follows:
[0037] (1) Magnesium alloy pretreatment: The magnesium alloy sample was cut into a size of 40 mm × 40 mm × 5 mm by wire cutting. The substrate was polished, rinsed and dried to remove machining marks on the surface of the magnesium alloy substrate and then set aside.
[0038] (2) Preparation of MOF: Weigh 8 g / L zinc nitrate and 20 g / L 2-methylimidazole and dissolve them in methanol respectively, and stir for 10 min. Then add 4 g / L succinic acid to the zinc nitrate solution, stir for 10 min, and adjust the pH value to 5 to obtain solution A; add 2 g / L phenol blue reagent to the 2-methylimidazole solution, stir for 10 min, and adjust the pH value to 9 to obtain solution B. Slowly pour solution A into solution B, mix and stir for 30 min, let stand for 12 h, and centrifuge the solution to collect the sediment;
[0039] (3) MOF modification: 10 g / L sodium dodecyl sulfate was dissolved in ethanol, and then the MOF prepared in step 2 was added and heated and stirred for 6 h. The solution was centrifuged, dried, collected, ground and sieved to obtain a MOF nanocontainer;
[0040] (4) Preparation of corrosion-resistant polymer coating on magnesium alloy: 2 g / L MOF nanocontainer was added to the varnish and uniformly dispersed in the coating solution by ultrasound to obtain a corrosion-resistant coating solution. This solution was sprayed on the surface of the magnesium alloy sample to prepare a coating with a thickness of 20 μm and allowed to stand at room temperature for 24 h. Subsequently, the sample was placed in an oven at 60 °C and dried for 24 h to complete the preparation of the corrosion-resistant polymer coating on the magnesium alloy.
[0041] The corrosion-resistant early warning polymer coating in the preparation method of a MOF-based magnesium alloy self-repairing and self-warning polymer coating provided in this embodiment is immersed in a 3.5wt.% NaCl solution for 300 days. The impedance diagram is as follows: Figure 2 shown.
[0042] Embodiment 3:
[0043] A method for preparing a MOF-based magnesium alloy self-repairing and self-warning polymer coating, the specific steps are as follows:
[0044] (1) Magnesium alloy pretreatment: The magnesium alloy sample was cut into a size of 40 mm × 40 mm × 5 mm by wire cutting. The substrate was polished, rinsed and dried to remove machining marks on the surface of the magnesium alloy substrate and then set aside.
[0045] (2) Preparation of MOF: Weigh 8 g / L zinc nitrate and 20 g / L 2-methylimidazole and dissolve them in methanol respectively, and stir for 10 min. Then add 4 g / L 8-hydroxyquinoline to the zinc nitrate solution, stir for 10 min and adjust the pH value to 5 to obtain solution A; add 2 g / L rhodamine to the 2-methylimidazole solution, stir for 10 min and adjust the pH value to 9 to obtain solution B. Slowly pour solution A into solution B, mix and stir for 30 min, let stand for 12 h, and centrifuge the solution to collect the sediment;
[0046] (3) MOF modification: 10 g / L sodium dodecyl sulfate was dissolved in ethanol, and then the MOF prepared in step 2 was added and heated and stirred for 6 h. The solution was centrifuged, dried, collected, ground and sieved to obtain a MOF nanocontainer;
[0047] (4) Preparation of corrosion-resistant polymer coating on magnesium alloy: 2 g / L MOF nanocontainer was added to the varnish and uniformly dispersed in the coating solution by ultrasound to obtain a corrosion-resistant coating solution. This solution was sprayed on the surface of the magnesium alloy sample to prepare a coating with a thickness of 20 μm and allowed to stand at room temperature for 24 h. Subsequently, the sample was placed in an oven at 60 °C and dried for 24 h to complete the preparation of the corrosion-resistant polymer coating on the magnesium alloy.
[0048] The corrosion-resistant early warning polymer coating in the preparation method of a MOF-based magnesium alloy self-repairing and self-warning polymer coating provided in this embodiment is immersed in a 3.5wt.% NaCl solution for 300 days. The impedance diagram is as follows: Figure 2 shown.
[0049] Embodiment 4:
[0050] A method for preparing a MOF-based magnesium alloy self-repairing and self-warning polymer coating, the specific steps are as follows:
[0051] (1) Magnesium alloy pretreatment: The magnesium alloy sample was cut into a size of 40 mm × 40 mm × 5 mm by wire cutting. The substrate was polished, rinsed and dried to remove machining marks on the surface of the magnesium alloy substrate and then set aside.
[0052] (2) Preparation of MOF: Weigh 8 g / L zinc nitrate and 20 g / L 2-methylimidazole and dissolve them in methanol respectively, and stir for 10 min. Then add 4 g / L benzotriazole to the zinc nitrate solution, stir for 10 min and adjust the pH value to 5 to obtain solution A; add 2 g / L phenolphthalein reagent to the 2-methylimidazole solution, stir for 10 min and adjust the pH value to 9 to obtain solution B. Slowly pour solution A into solution B, mix and stir for 30 min, let stand for 12 h, and centrifuge the solution to collect the sediment;
[0053] (3) MOF modification: 10 g / L sodium dodecyl sulfate was dissolved in ethanol, and then the MOF prepared in step 2 was added and heated and stirred for 6 h. The solution was centrifuged, dried, collected, ground and sieved to obtain a MOF nanocontainer;
[0054] (4) Preparation of corrosion-resistant polymer coating on magnesium alloy: 2 g / L MOF nanocontainer was added to the varnish and uniformly dispersed in the coating solution by ultrasound to obtain a corrosion-resistant coating solution. This solution was sprayed on the surface of the magnesium alloy sample to prepare a coating with a thickness of 20 μm and allowed to stand at room temperature for 24 h. Subsequently, the sample was placed in an oven at 60 °C and dried for 24 h to complete the preparation of the corrosion-resistant polymer coating on the magnesium alloy.
[0055] The corrosion-resistant early warning polymer coating in the preparation method of a MOF-based magnesium alloy self-repairing and self-warning polymer coating provided in this embodiment is immersed in a 3.5wt.% NaCl solution for 300 days. The impedance diagram is as follows: Figure 2shown.
[0056] Embodiment 5:
[0057] A method for preparing a MOF-based magnesium alloy self-repairing and self-warning polymer coating, the specific steps are as follows:
[0058] (1) Magnesium alloy pretreatment: The magnesium alloy sample was cut into a size of 40 mm × 40 mm × 5 mm by wire cutting. The substrate was polished, rinsed and dried to remove machining marks on the surface of the magnesium alloy substrate and then set aside.
[0059] (2) Preparation of MOF: Weigh 8 g / L zinc nitrate and 20 g / L 2-methylimidazole and dissolve them in methanol respectively, and stir for 10 min. Then add 8 g / L tartaric acid to the zinc nitrate solution, stir for 10 min and adjust the pH value to 5 to obtain solution A; add 4 g / L phenolphthalein reagent to the 2-methylimidazole solution, stir for 10 min and adjust the pH value to 9 to obtain solution B. Slowly pour solution A into solution B, mix and stir for 30 min, let stand for 12 h, and centrifuge the solution to collect the sediment;
[0060] (3) MOF modification: 10 g / L sodium dodecyl sulfate was dissolved in ethanol, and then the MOF prepared in step 2 was added and heated and stirred for 6 h. The solution was centrifuged, dried, collected, ground and sieved to obtain a MOF nanocontainer;
[0061] (4) Preparation of corrosion-resistant polymer coating on magnesium alloy: 2 g / L MOF nanocontainer was added to the varnish and uniformly dispersed in the coating solution by ultrasound to obtain a corrosion-resistant coating solution. This solution was sprayed on the surface of the magnesium alloy sample to prepare a coating with a thickness of 20 μm and allowed to stand at room temperature for 24 h. Subsequently, the sample was placed in an oven at 60 °C and dried for 24 h to complete the preparation of the corrosion-resistant polymer coating on the magnesium alloy.
[0062] The corrosion-resistant early warning polymer coating in the preparation method of a MOF-based magnesium alloy self-repairing and self-warning polymer coating provided in this embodiment is immersed in a 3.5wt.% NaCl solution for 300 days. The impedance diagram is as follows: Figure 2 shown.
[0063] Embodiment 6:
[0064] A method for preparing a MOF-based magnesium alloy self-repairing and self-warning polymer coating, the specific steps are as follows:
[0065] (1) Magnesium alloy pretreatment: The magnesium alloy sample was cut into a size of 40 mm × 40 mm × 5 mm by wire cutting. The substrate was polished, rinsed and dried to remove machining marks on the surface of the magnesium alloy substrate and then set aside.
[0066] (2) Preparation of MOF: Weigh 8 g / L zinc nitrate and 20 g / L 2-methylimidazole and dissolve them in methanol respectively, and stir for 10 min. Then add 6 g / L tartaric acid to the zinc nitrate solution, stir for 10 min and adjust the pH value to 5 to obtain solution A; add 3 g / L phenolphthalein reagent to the 2-methylimidazole solution, stir for 10 min and adjust the pH value to 9 to obtain solution B. Slowly pour solution A into solution B, mix and stir for 30 min, let stand for 12 h, and centrifuge the solution to collect the sediment;
[0067] (3) MOF modification: 10 g / L sodium dodecyl sulfate was dissolved in ethanol, and then the MOF prepared in step 2 was added and heated and stirred for 6 h. The solution was centrifuged, dried, collected, ground and sieved to obtain a MOF nanocontainer;
[0068] (4) Preparation of corrosion-resistant polymer coating on magnesium alloy: 2 g / L MOF nanocontainer was added to the varnish and uniformly dispersed in the coating solution by ultrasound to obtain a corrosion-resistant coating solution. This solution was sprayed on the surface of the magnesium alloy sample to prepare a coating with a thickness of 20 μm and allowed to stand at room temperature for 24 h. Subsequently, the sample was placed in an oven at 60 °C and dried for 24 h to complete the preparation of the corrosion-resistant polymer coating on the magnesium alloy.
[0069] The corrosion-resistant early warning polymer coating in the preparation method of a MOF-based magnesium alloy self-repairing and self-warning polymer coating provided in this embodiment is immersed in a 3.5wt.% NaCl solution for 300 days. The impedance diagram is as follows: Figure 2 shown.
[0070] Comparative Example 1:
[0071] The preparation method of the magnesium alloy polymer coating comprises the following specific steps:
[0072] (1) The magnesium alloy sample was cut into a size of 40 mm × 40 mm × 5 mm, and the substrate was polished with 240#, 400#, 600#, 800#, 1000#, and 2000# water-abrasive sandpaper in sequence, and then rinsed and dried with alcohol to remove machining marks on the surface of the magnesium alloy substrate, and then set aside;
[0073] (2) Preparation of magnesium alloy polymer coating: Spray the varnish on the surface of the magnesium alloy sample to prepare a coating with a thickness of 20 μm. Leave it at room temperature for 24 hours, then bake the sample in an oven at 60°C for 24 hours. After the coating is fully dried, the preparation of the magnesium alloy polymer coating is completed.
[0074] The impedance diagram of the polymer coating in the preparation method of a MOF-based magnesium alloy self-repairing self-warning polymer coating provided in this comparative example is as follows: Figure 3 shown.
[0075] observe Figure 1 The microscopic morphology of the MOF nanocontainer is shown in Figure 2. The MOF particle size is about 80-120nm. Figure 2 and Figure 3 The addition of MOF nanocontainers effectively improves the long-term corrosion resistance of the polymer coating. After the ordinary polymer coating is immersed in 3.5wt.%NaCl solution for 100 days, the low-frequency impedance value has dropped to 10 3 Ω / cm -2 After immersion for 300 days, the low-frequency impedance of the coating doped with MOF nanocontainers remained at 10 6 Ω / cm -2 The above results indicate that the corrosion inhibitor effectively inhibits corrosion and enables the coating to have self-healing function. Figure 4 It can be seen that as the immersion time increases, the UV intensity of the warning agent in the solution also increases, which ensures the self-warning performance of the coating. In summary, the comprehensive performance of the coating of the embodiment of the present invention is better than that of the coating of the comparison group.
[0076] The technical scope of the present invention is not limited to the contents in the above description. Those skilled in the art can make various deformations and modifications to the above embodiments without departing from the technical idea of the present invention, and these deformations and modifications should all fall within the protection scope of the present invention.
Claims
1. A method for preparing a MOF-based magnesium alloy self-repairing and self-warning polymer coating, characterized in that: The following steps are involved: S1. Pretreatment of magnesium alloy: Cut the magnesium alloy sample into 40mm×40mm×5mm size by wire cutting. Wash and dry the polished substrate with deionized water to remove the machining marks on the surface and set aside; S2. MOF preparation: zinc nitrate and 2-methylimidazole were dissolved in an organic solvent respectively and stirred for 10 minutes; then, a corrosion inhibitor was added to the zinc nitrate solution, and the pH value was adjusted to 5 after stirring for 10 minutes to obtain solution A; Add the warning agent to the 2-methylimidazole solution, stir for 10 minutes and then adjust the pH value to 7 to obtain solution B; Slowly pour solution A into solution B, mix and stir for 30 minutes, let stand for 12 hours, centrifuge the suspension and collect the precipitate; S3, MOF modification: dissolving the surfactant in an organic solvent, then adding the MOF prepared in step 2, and stirring at 60°C for 6 hours; centrifuging the solution, drying it, collecting it, grinding and sieving it, to obtain a MOF nanocontainer; S4, preparation of corrosion-resistant polymer coating for magnesium alloy: adding the MOF nanocontainer obtained in step 3 to the varnish, and uniformly dispersing it in the coating solution by ultrasound to obtain a corrosion-resistant coating solution; The solution was sprayed on the surface of the magnesium alloy sample and allowed to stand at room temperature for 24 hours; then, the sample was placed in a 60°C oven and dried for 24 hours to complete the preparation of the corrosion-resistant polymer coating on the magnesium alloy.
2. The method for preparing a MOF-based magnesium alloy self-repairing and self-warning polymer coating according to claim 1, characterized in that: The grinding method is to use 240#, 400#, 600#, 800#, 1000#, and 2000# roughness water-abrasive sandpaper to grind the surface of the magnesium alloy substrate in sequence until the surface of the magnesium alloy substrate is smooth and flat.
3. The method for preparing a MOF-based magnesium alloy self-repairing and self-warning polymer coating according to claim 1, characterized in that: The organic solvent is one or a mixture of methanol, ethanol and ethylene glycol; The corrosion inhibitor is one or more of succinic acid, benzotriazole, methionine, tartaric acid, and 8-hydroxyquinoline; The warning agent is one or more of phenolphthalein, rhodamine, and phenol blue reagent; The surfactant is one or more of sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, sodium dodecyl sulfonate, and sodium lauryl sulfate.
4. The method for preparing a MOF-based magnesium alloy self-repairing and self-warning polymer coating according to claim 1, characterized in that: Stirring method: the stirring speed is controlled at 200-250rpm / min.
5. The method for preparing a MOF-based magnesium alloy self-repairing and self-warning polymer coating according to claim 1, characterized in that: Adjust pH using sodium hydroxide or nitric acid.
6. The method for preparing a MOF-based magnesium alloy self-repairing and self-warning polymer coating according to claim 1, characterized in that: The drug contents for preparing MOF particles are as follows: 5-20 g / L zinc nitrate, 5-50 g / L 2-methylimidazole, 1-5 g / L corrosion inhibitor, 1-5 g / L early warning agent, and 1-20 g / L surfactant.
7. The method for preparing a MOF-based magnesium alloy self-repairing and self-warning polymer coating according to claim 1, characterized in that: The grinding and sieving method was to grind the MOF particles for 20 min using an agate grinding mortar, and then sieve the particles using a sieve with a particle size of 3000 mesh.
8. The method for preparing a MOF-based magnesium alloy self-repairing and self-warning polymer coating according to claim 1, characterized in that: The drying method is to use a vacuum drying oven to dry the powder. The setting temperature of the vacuum drying oven is 60-100°C and the heating time is 4-6h.
9. The method for preparing a MOF-based magnesium alloy self-repairing and self-warning polymer coating according to claim 1, characterized in that: The ratio of various substances in the corrosion-resistant coating solution is: MOF particles are 1-10g / L.
10. The method for preparing a MOF-based magnesium alloy self-repairing and self-warning polymer coating according to claim 1, characterized in that: The spraying method is aerosol spraying, and the process parameters are: air pressure 0.2-0.4Mpa, spraying distance 100-300mm, flow rate 20-100mL / min, atomizing nozzle 1.3-2.0mm, spray gun speed 50-400mm / s, coating spraying times 1-10 times; polymer coating thickness is 10-50μm.
Citation Information
Patent Citations
A self-repairing anti-corrosion coating based on MOF composite filler and its preparation method and use
CN118185441B
Cited By
Preparation method of magnesium alloy micro-arc oxidation coating integrating surface hydrophobicity, corrosion self-warning and self-repairing and product thereof
CN122235799A